A Study of the Influence of Sodium Alginate Molecular Weight and Its Crosslinking on the Properties of Potato Peel Waste-Based Films - Mohsen Sadeghi-Shapourabadi; Mathieu Robert; Said Elkoun (Applied Sciences, 2025)
This study develops a sustainable biopolymer film derived from potato peel waste (PW), enhanced with low- and high-viscosity sodium alginate (SA) through a solution casting method. The effect of calcium chloride crosslinking on the PW/SA composites was also evaluated. Scanning electron microscopy (SEM) analysis revealed that SA incorporation improved the film’s cohesion and uniformity, with both low- and high-viscosity SA showing nearly similar effects. Both the addition of SA and crosslinking led to enhanced tensile strength, as well as improved moisture barrier properties, by lowering the water vapor permeability (WVP) factor. The inclusion of high-viscosity SA (hvSA) resulted in superior mechanical and moisture barrier properties compared to the low-viscosity SA (lvSA), achieving a tensile strength of 5.34 MPa, with a 68% improvement compared to the pure PW film. The WVP analysis showed that hvSA had a superior impact, leading to a 32% reduction in WVP compared to the pure film. Crosslinking further boosted the tensile strength and moisture barrier properties. The crosslinked hvSA/PW composite shows the highest tensile strength among all samples, measuring 6.47 MPa, which accounts for a 104% enhancement compared to the pure film. It also led to a 34% reduction in WVP, reaching a value of 1.58 × 10−12 g/(Pa·cm·s). The findings demonstrate that PW/SA composites, especially the crosslinked hvSA/PW, offer the highest mechanical and barrier properties, making them suitable for biodegradable packaging and biomedical applications.